A rare presentation of Zinner syndrome as recurrent epididymitis: A case report - Nabil CN Khalil; Mohammed Ayyad; Maram Albandak; Anas Aljundi; Mohamad Qabaja (SAGE Open Medical Case Reports, 2023)
Zinner syndrome is a rare congenital malformation characterized by ipsilateral renal agenesis, atresia of the ejaculatory duct, and cystic distension of the seminal vesicles. Symptoms typically arise in adolescence or adulthood and may include painful urination, perineal discomfort, and post-ejaculatory pain. Diagnosis, often made between the ages of 20 and 50 years, involves differentiating Zinner syndrome from other cystic disorders using techniques such as cystoscopy, MRI, intravenous urography, and transrectal ultrasound. Treatment varies based on symptom severity, ranging from conservative approaches to invasive surgeries. Regular follow-up is essential to identify complications and preserve fertility. Herein, we present a 27-year-old male with recurrent scrotal swelling and erythema incidentally diagnosed with Zinner syndrome. The patient had a history of recurrent epididymitis and was found to have cystic dilatation of the seminal vesicle, ipsilateral renal agenesis, and obstruction of the left ejaculatory duct on imaging. Given the patient’s mild symptoms, he was managed conservatively with antibiotics and pain medication, resulting in significant improvement.